The Use of Botulinum Toxin Injection for Brachial Plexus Birth Injuries: A Systematic Review of the Literature - Buchanan, Patrick J. (Hand (N Y), 2018)
Background: Most brachial plexus birth injuries (BPBIs) are caused by traction on the brachial plexus during a difficult delivery. Fortunately, the possibility of complete recovery from such an incident is relatively high, with only 10% to 30% of patients having prolonged and persistent disability. These patients have muscle imbalances and co-contractions typically localized around the shoulder and elbow. These imbalances and co-contractures cause abnormal motor performances and bone/joint deformities. Typically, physical/occupational therapies are the conventional therapeutic modalities but are often times inadequate. Botulinum toxin A (BTX-A) injections into targeted muscles have been used to combat the muscular imbalances and co-contractions. Methods: With compliance to PRISMA guidelines, a systematic review was performed to identify studies published between 2000 and 2017 that used BTX-A to treat neonatal brachial plexus palsies. Results: Ten studies were included, involving 325 patients. Three groups of indications for the use of BTX-A were identified: (1) internal rotation/adduction contracture of the shoulder; (2) elbow flexion lag/elbow extension lag; and (3) forearm pronation contracture. Conclusions: The included studies show an overall beneficial effect of BTX-A in treating co-contractures seen in patients with BPBI. Specifically, BTX-A is shown to reduce internal rotation/adduction contractures of the shoulder, elbow flexion/extension contractures, and forearm pronation contractures. These beneficial effects are blunted when used in older patients. Nevertheless, BTX-A is a useful treatment for BPBIs with a relatively low-risk profile.